CAUSES, MORBIDITY AND MORTALITY OF UPPER GASTROINTESTINAL BLEEDING (UGIB) AMONGST HOSPITALIZED PATIENTS (The Research of Medical Science Review, 2025)
Background: Upper gastrointestinal bleeding is the term used to describe hemorrhage that develops in between the esophagus and the ligament of Treitz. Objective: The aim of the study was to determine Causes, Mortality and Morbidity of Upper GIT Bleeding amongst Hospitalized individuals Materials and method: The present research was conducted from September 2023 to march 2024 at the Gastroenterology department, Bolan Medical Complex hospital, Quetta Balochistan after taking permission from the ethics review committee of the institute. A total of 224 participants were selected in this study. To identify the risk variables responsible for an increase in patient mortality and morbidity, all patients were observed for a maximum of two weeks. All of the participants were transferred to their major ward for further assessment following endoscopy. The gathered data was analyzed using SPSS 24.0. Results: A total of 224 individuals were included in this study out of which 145(64.7%) were male and 79(35.26%) were female. According to the clinical profile, 35 participants (15·6%) experienced non-specific symptoms, whereas 187 participants (83.4%) had both melena and hematemesis. According to endoscopy findings, Oesophageal varices were the most prevalent cause of upper gastrointestinal bleeding, accounting for 132 cases (58.92%), followed by peptic ulcer in 33 cases (14.7%), gastritis in 22 cases (9.82%), and esophagitis in 20 cases (8.9%),. 40 patients (17.85%) had low risk, 128 patients (57.14%) had moderate risk, and 56 patients (25%) had high risk based on the Rockall score. Our research had a total death rate of 15 (6.69%). Mortality and Rockall score were shown to be significantly correlated (p=0.001). In the high-risk group of Rockall score, a high mortality rate of 10 (4.46. %) was noted. Conclusion: Our study concludes that the most frequent cause for upper gastrointestinal bleeding was variceal bleeding. The second most frequent etiology for upper gastrointestinal bleeds was peptic ulcer. Additionally, our research demonstrates that the Rockall score is a reliable indicator of outcome for individuals with upper gastrointestinal bleeding.